2022
DOI: 10.1002/pits.22785
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the COVID‐19 public health emergency: The usefulness of an online brief psychological intervention with Italian university students

Abstract: The COVID‐19 pandemic has brought about new stressors on university students, with a negative impact on their mental health and well‐being. The purpose of this study was to examine the usefulness of a brief psychodynamically oriented intervention on general functioning by investigating changes in symptoms of depression, anxiety, hopelessness, and burnout. The sample was comprised of 67 university students (22.4% males), with a mean age of 23.27 (standard deviation (SD) = 3.27), who asked for psychological help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…First, our results revealed a decrease in the Symptom Distress (SD) dimension after the counseling intervention. The present findings are in line with numerous studies showing the effectiveness of university counseling services in reducing anxiety and depressive symptoms ( Østergård et al, 2017 ; Barnett et al, 2021 ; Cerutti et al, 2022 , 2023 ). Biasi et al (2017) , for example found, in a sample of students who had undergone counseling, not only a significant decrease in internalizing disorders such as anxiety and depression, but also a substantial improvement in all three dimensions of the OQ-45.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, our results revealed a decrease in the Symptom Distress (SD) dimension after the counseling intervention. The present findings are in line with numerous studies showing the effectiveness of university counseling services in reducing anxiety and depressive symptoms ( Østergård et al, 2017 ; Barnett et al, 2021 ; Cerutti et al, 2022 , 2023 ). Biasi et al (2017) , for example found, in a sample of students who had undergone counseling, not only a significant decrease in internalizing disorders such as anxiety and depression, but also a substantial improvement in all three dimensions of the OQ-45.…”
Section: Discussionsupporting
confidence: 93%
“…This may be explained by a more positive attitude toward psychological support and a greater tendency to seek it among women, relative to men ( Elhai et al, 2008 ; Nam et al, 2010 ). However, as also found by Cerutti et al (2023) , no sex- and age-related differences were found in our study in measuring the overall well-being of OQ-45 total scores.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…If guided support was synchronous (n = 2; Cerutti et al, 2022;Harra & Vargas, 2023), we found reduced depression symptoms. If guided support was asynchronous (n = 12) or both synchronous and asynchronous (n = 9), results suggest mixed benefit in depressive outcomes.…”
Section: Depression Symptomsmentioning
confidence: 74%
“…Studies with healthy Italian participants conducted at the beginning of the COVID-19 pandemic also reported that participants’ depression, anxiety, and obsessive-compulsive symptoms worsened compared to before the lockdown ( Mariani et al, 2020 , 2021 ). Another comparative study of Italian college students before and after COVID-19 found that clinical symptoms such as depressive, anxiety, and psychotic symptoms increased significantly after pandemic ( Cerutti et al, 2022 , 2023 ). Factors such as reduced social interaction, heightened loneliness, fears of disease transmission, and increased uncertainty have could lead to elevated levels of depression, anxiety, and psychological distress ( Fiorillo and Gorwood, 2020 ; Fountoulakis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%